Implikasi Hukum Penyelamatan Kredit Bermasalah melalui Restrukturisasi di Indonesia - Ninik Zakiyah (Fakultas Hukum, Universitas Internasional Batam, 2021)
Restructuring is commonly used in banking to handle non-performing loans. However, each bank has its own policies in its implementation. This article aims to find out how debtors need to pay attention to the restructuring mechanism, and what are the implications of this method for the debtor. This research is included in normative law research, with a conceptual and statutory approach, which uses secondary data from primary, secondary and tertiary legal materials which are then analyzed qualitatively. The results obtained indicate that the factors causing problem loans can occur from internal (bank) and external (debtor) factors. Through credit restructuring, it can be chosen because it is better able to provide a solution between the two, because it is preceded by negotiation between the parties so that the interests of both are conveyed. Restructuring can release the threat of execution of the mortgage object for the debtor, but on the other hand it also has implications for the debtor to settle credit for a long period of time.